Analisis Pengaruh Intensitas Kebisingan terhadap Kelelahan Kerja dan Kinerja Mahasiswa dengan Metode Regresi Linear dan Uji Korelasi (Studi Kasus di Laboratorium Teknik Industri Universitas Sarjanawiyata Tamansiswa) - Retno Widiastuti; Dian Tiara Rezalti; Dede Yulian (Universitas Sarjanawiyata Tamansiswa, 2022)
Work fatigue is a state of the body that has decreased performance. One of the causes of work fatigue is the condition of a noisy work environment. The high noise factor can cause work fatigue which affects the decrease in the level of concentration when doing work. The research objective was to determine the effect of noise intensity on work fatigue and student performance. The experiment was carried out on 30 students as respondents who were in the Industrial Engineering Laboratory of the Universitas Sarjanawiyata Tamansiswa. Students are asked to work on Academic Potential Test questions in 3 different noise intensity variables which are divided into 3 sessions. The first session had a noise intensity of 63.3 dB, the second session 84.4 dB and the third session 91.6 dB. The data obtained were analyzed by Simple Linear Regression and Correlation Test. The results of the study stated that the variable effect of noise on work fatigue obtained a significance value of 0.021. The significance value of 0.021 is less than 0.05 which means that there is a significant effect of noise on student work fatigue. Then in the variable effect of noise on student performance, a significance value of 0.012 is obtained. The significance value of 0.012 is less than 0.05 which means that there is a significant effect of noise on student performance. For the correlation test, the Pearson correlation values were 0.999 and -1.000, which means that the strength of the relationship between the two variables has a perfect correlation.